POTENSI PENYERAPAN KARBON PADA KARET POLA TUMPANGSARI TANAMAN HUTAN - Sahuri Sahuri (Jurnal Hutan Tropis, 2016)
Rubber plant (Hevea brasilliensis) has a very big role in the economy and the absorption of CO2. Rubber plants as well as forest plants capable of processing CO2 as a carbon source that is used for photosynthesis. CO2 absorption can be enhanced through the implementation of intercropping pattern rubber and forest plant. This study aims to determine the potential for carbon sequestration in intercropping pattern rubber and forest plant. The experiment was conducted at the Sembawa Research Station, South Sumatra, with three cropping pattern (PT), namely PT1: rubber plants + teak (Tectona grandis), PT2: rubber plants + trembesi (Samanea saman), PT3: rubber plant monocultures, PT4: teak monocultures, and PT5: trembesi plant monocultures. Measurement of carbon reserves consist of tree biomass and soil organic matter. The results showed that the amount of absorption of CO2/year in the rubber plantations for 10 years for PT1, PT2, PT3, PT4, and PT5, respectively were 86.46 tons/ha, 125.90 tons / ha, 77.90 tons/ha, 36.26 tons/ha and 49.03 tons/ha. The addition of carbon sequestration for 10 years due to intercrop rubber and forest plant was 30.13% or 49.17 tons CO2/ha compared to the rubber plant monocultures.Tanaman karet (Hevea brasilliensis) memiliki peran yang sangat besar dalam perekonomian dan penyerapan CO2. Tanaman karet seperti halnya tanaman hutan mampu mengolah CO2 sebagai sumber karbon yang digunakan untuk fotosintesis. Penyerapan CO2 dapat ditingkatkan melalui penerapan pola tumpangsari karet dan tanaman hutan. Penelitian ini bertujuan untuk mengetahui potensi penyerapan karbon pada pola tumpangsari karet dan tanaman hutan. Penelitian dilaksanakan di kebun percobaan Balai Penelitian Sembawa, Sumatra Selatan, dengan tiga pola tanam (PT), yaitu PT1: tanaman karet + jati (Tectona grandis), PT2: tanaman karet + trembesi (Samanea saman), PT3: tanaman karet monokultur, PT4: tanaman jati monokultur, dan PT5: tanaman trembesi monokultur. Pengukuran cadangan karbon terdiri dari biomasa pohon dan bahan organik tanah. Hasil penghitungan menunjukan bahwa jumlah penyerapan CO2/tahun di perkebunan karet selama 10 tahun untuk PT1, PT2, PT3, PT4, dan PT5 masing-masing adalah 86,46 ton/ha, 125,90 ton/ha, 77,90 ton/ha, 36,26 ton/ha, dan 49,03 ton/ha. Penambahan penyerapan karbon selama 10 tahun akibat adanya pola tumpang sari karet dan tanaman hutan adalah 30,13% atau 49,17 ton CO2/ha dibandingkan tanaman karet monokultur.